Further Hilbert-Schmidt Numerical Radius Inequalities for 2 × 2 Operator Matrices. (4th April 2023) - Aici, Soumia; Frakis, Abdelkader; Kittaneh, Fuad
Abstract: We give several bounds for the Hilbert-Schmidt numerical radii of 2 × 2 operator matrices. Some of these bounds are refinements of the existing ones.